Effect of N incorporation on the characteristics of InSbN P–N diodes - Pham, H. T. (2013)
We report on the effect of N incorporation in the characteristics of the 2 μm thick InSbN photoabsorption layer of a p–n diode grown by molecular beam epitaxy using a radio-frequency plasma-assisted nitrogen source. As compared to N free InSb layer, the absorption wavelength extends to near 9 μm. On the other hand, high reverse dark current and series resistances are observed in the electrical characteristics of the InSbN diode which are contributed with the presence of planar growth defects. These results will be useful to those working on midinfrared photodetectors.